Increased Thermal Sensitivity of a Tropical Marine Gastropod Under Combined CO2 and Temperature Stress - Minuti, Jay J.; Corra, Charlee A.; Helmuth, Brian S.; Russell, Bayden D. (Frontiers in Marine Science, 2021)
The ability of an organism to alter its physiology in response to environmental conditions offers a short-term defence mechanism in the face of weather extremes resulting from climate change. These often manifest as multiple, interacting drivers, especially pH and temperature. In particular, decreased pH can impose constraints on the biological mechanisms which define thermal limits by throwing off energetic equilibrium and diminishing physiological functions (e.g., in many marine ectotherms). For many species, however, we do not have a detailed understanding of these interactive effects, especially on short-term acclimation responses. Here, we investigated the metabolic plasticity of a tropical subtidal gastropod (Trochus maculatus) to increased levels of CO2 (700 ppm) and heating (+3°C), measuring metabolic performance (Q10 coefficient) and thermal sensitivity (temperature of maximum metabolic rate [TMMR], and upper lethal temperature [ULT]). Individuals demonstrated metabolic acclimation in response to the stressors, with TMMR increasing by +4.1°C under higher temperatures, +2.7°C under elevated CO2, and +4.4°C under the combined stressors. In contrast, the ULT only increased marginally in response to heating (+0.3°C), but decreased by -2.3°C under CO2, and -8.7°C under combined stressors. Therefore, although phenotypic plasticity is evident with metabolic acclimation, acute lethal temperature limits seem to be less flexible during short-term acclimation.